2021
DOI: 10.1111/1750-3841.15916
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic, osmovacuum, sonication, and osmosonication pretreatment on the infrared drying of Ginkgo seed slices: Mass transfer, mathematical modeling, drying, and rehydration kinetics and energy consumption

Abstract: This study evaluated the mass transfer, drying, and rehydration kinetics (drying and rehydration curve, moisture diffusivity [Deff]), energy consumption (specific energy consumption [SEC], moisture extraction rate (MER), and specific moisture extraction rate [SMER]), and mathematical modeling of infrared dried Ginkgo biloba seed (GBS) using the various nonthermal pretreatments namely: osmotic (OS), osmovacuum (V + OS), ultrasound (US, ginkgo seed immersed in a distilled water with US), and osmosonication (US +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Drying curves exhibited a continuous falling rate pattern, which corroborates that moisture mobility was governed by diffusion. Similar scenarios were reported during the drying of Ginkgo biloba seeds [49] , ginger slices [54] , and scallion cylinders [48] . MR curves of pretreated slices were more declined compared to the control group.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Drying curves exhibited a continuous falling rate pattern, which corroborates that moisture mobility was governed by diffusion. Similar scenarios were reported during the drying of Ginkgo biloba seeds [49] , ginger slices [54] , and scallion cylinders [48] . MR curves of pretreated slices were more declined compared to the control group.…”
Section: Resultssupporting
confidence: 72%
“…Another explanation could be that the effect of ultrasound was maximized in distilled water than in sucrose solution since cavitation is reduced in viscous solutions [16] . Boateng & Yang [49] and Fernandes et al [43] reported similar trends between US and US-OD during the dehydration of Ginkgo biloba seeds and pineapple slices, respectively.
Fig.
…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations